2019
DOI: 10.4236/ojcm.2019.93019
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Effect of Agro Waste Ash as Reinforcement on Aluminium Base Metal Matrix Composites

Abstract: In the present day availability of agricultural waste products is very huge quantity. Most of the industries prefer Metal matrix composite (MMC) due to their density, high strength to weight ratio, hardness, corrosion resistance, fatigue and creep resistance. Hence they are widely used in structural applications along with aerospace and automobile industry, marine, sports, electronic and automation industries. In the present paper a study is focused on the mechanical, tribological and corrosion behavior of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…This can be attributed to their enormous qualities which differ greatly from those of aluminium. Despite the fact that aluminium has light weight, it possesses low strength and low melting point which makes it unfit in areas of applications where high strength is needed (Bahrami, Soltani, Pech-Canul, & Guti errez, 2016;Kulkarni et al, 2019). Research has shown that AMCs possess high specific strength, yield strength and ultimate tensile strength.…”
Section: Synopsis Of Selected Results and Discussion From Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…This can be attributed to their enormous qualities which differ greatly from those of aluminium. Despite the fact that aluminium has light weight, it possesses low strength and low melting point which makes it unfit in areas of applications where high strength is needed (Bahrami, Soltani, Pech-Canul, & Guti errez, 2016;Kulkarni et al, 2019). Research has shown that AMCs possess high specific strength, yield strength and ultimate tensile strength.…”
Section: Synopsis Of Selected Results and Discussion From Literaturementioning
confidence: 99%
“…Research has shown that AMCs possess high specific strength, yield strength and ultimate tensile strength. Other properties include; increased corrosion resistance, low wear rate, increased coefficient of friction, increased hardness, improved weldability, and high strength to volume ratio (Al-Fadhalah, Almazrouee, & Aloraier, 2014;Kulkarni et al, 2019). The addition of reinforcements to aluminium improves the properties of the base metal.…”
Section: Synopsis Of Selected Results and Discussion From Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the development of agrowaste AMC's is quite beneficial. The use of agrowaste materials results in formation of low cost and lightweight composites without compromising their mechanical and tribological properties [28,29]. However, there is a limited understanding of their service performance, thus restricts their utilization options for their wider use in applications.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Similarly, periwinkle shell is obtained from the consumption of periwinkle ( Taulbee et al., 2009 ; Nwabue et al., 2017 ) and rice husk is derived from the processing of rice ( Ikelle et al., 2017 ). Studies have shown that when these materials are compacted, they can be highly beneficial to many domestic and industrial processes ( Kulkarni et al., 2019 ; Sundari et al., 2019 ). Biomass waste have been considered as a renewable alternative source of energy, which will reduce dependency on fossil fuel ( Adeleke et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%